2020
DOI: 10.1002/zoo.21559
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the season and reproductive status on fecal reproductive and adrenocortical steroid metabolites in zoo Cuban crocodiles (Crocodylus rhombifer)

Abstract: Conservation strategies for crocodilians often include captive breeding to create stable assurance populations. Evaluating adrenal and gonadal hormone patterns can provide animal managers with data to more effectively monitor animal welfare and reproductive status. This study evaluated the effects of season (breeding, nesting, or off), sex (male and female), and reproductive status of females (egg-laying/housed with a male or non-laying/housed solo) on concentrations of fecal glucocorticoid metabolite (FGM), f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…Although we found that increased FGM was associated with increased levels of disturbance in these snakes, we urge caution in the design of studies using FGM to assess welfare in reptiles. Gastrointestinal passage time in reptiles makes it difficult to assess real-time stress responses, as it represents an average value pooled in the gut of the animal over a more prolonged period than is typically the case in mammals or birds [59,64]. In this study, there was a significant positive association between the number of days since the last feeding and FGM concentrations.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Although we found that increased FGM was associated with increased levels of disturbance in these snakes, we urge caution in the design of studies using FGM to assess welfare in reptiles. Gastrointestinal passage time in reptiles makes it difficult to assess real-time stress responses, as it represents an average value pooled in the gut of the animal over a more prolonged period than is typically the case in mammals or birds [59,64]. In this study, there was a significant positive association between the number of days since the last feeding and FGM concentrations.…”
Section: Discussionmentioning
confidence: 65%
“…Snakes respond to stress by activating the hypothalamic-pituitaryadrenal (HPA-) axis, which releases corticosterone into the blood [55]. Fecal glucocorticoid metabolites (FGM) can be measured non-invasively in animal feces [49], a technique that is becoming increasingly popular as a tool for evaluating reptile welfare [48,49,[56][57][58][59][60][61][62][63][64]. Many factors can influence FGM levels, such as diet and metabolic rate [51,65,66].…”
Section: Introductionmentioning
confidence: 99%
“…The use of non-invasive endocrine monitoring techniques, through the collection of faeces, urine and hair, hold several advantages above the commonly used, invasive blood collection, including (1) minimal human-animal interaction, (2) the ability to collect repeated samples over prolonged periods with minimal effort (Whitham and Wielebnowski 2013) and (3) hormone metabolite concentrations assessed in faeces are less affected by episodic fluctuations in hormone secretions due to the pooling of metabolites within the gut prior to excretion (Kersey and Dehnhard 2014;Russell et al 2012). Several studies have used noninvasive faecal glucocorticoid metabolite (fGCM) monitoring to assess the level of physiological stress experienced by reptiles in response to direct human-animal interaction (Borgmans et al 2018;Kalliokoski et al 2012;Rittenhouse et al 2005) or seasonal changes in social and reproductive parameters (Augustine et al 2020;West and Klukowski 2018).…”
Section: )mentioning
confidence: 99%
“…However, for the crocodilians, only two studies have been done so far to measure fGCM concentrations: one on Nile crocodiles ( Ganswindt et al. , 2014 ) and the other on Cuban crocodiles ( Crocodylus rhombifer ) ( Augustine et al. , 2020 ).…”
Section: Introductionmentioning
confidence: 99%